LINGUISTIC REALIZATION OF REQUESTS IN ENGLISH AND JAVANESE PERFORMED BY JAVANESE EFL LEARNERS - Septiani, Swastika (English Education Journal, 2014)
Located in junior high school (SMP) 35 Semarang, this study applied STAD in giving solution to studentsâ problems in reading comprehension. Those problems were written in three statements: first, what the problems in reading comprehension faced by the eighth graders of SMP 35 Semarang were; second, how to implement this strategy in the practice of reading comprehension; and third, how STAD could improve the practice of reading comprehension to the eighth graders of junior high school. The method used in this study was qualitative. The data was gained through observing, giving questionnaire, and interviewing students. The major problem was the students had low achievement and motivation which was stimulated by the lack of having effective practice. Therefore, improving their practice was the way to solve the problems. Using STAD in the practices were done in three cycles covering materialsâ arrangement and behavior improvement which stimulated better condition for studying. This condition affected studentsâ extrinsic motivation and behavior for studying. After three cycles, this strategy helped the students have behavior improvement and higher achievement.